Combining integrated genomics and functional genomics to dissect the biology of a cancer‐associated, aberrant transcription factor, the ASPSCR1–TFE3 fusion oncoprotein3. Issue 5 (5th March 2013) - Kobos, Rachel; Nagai, Makoto; Tsuda, Masumi; Merl, Man Yee; Saito, Tsuyoshi; Laé, Marick; Mo, Qianxing; Olshen, Adam; Lianoglou, Steven; Leslie, Christina; Ostrovnaya, Irina; Antczak, Christophe; et al.
Abstract Oncogenic rearrangements of the TFE3 transcription factor gene are found in two distinct human cancers. These include ASPSCR1–TFE3 in all cases of alveolar soft part sarcoma (ASPS) and ASPSCR1–TFE3, PRCC‐TFE3, SFPQ‐TFE3 and others in a subset of paediatric and adult RCCs. Here we examined the functional properties of the ASPSCR1–TFE3 fusion oncoprotein, defined its target promoters on a genome‐wide basis and performed a high‐throughput RNA interference screen to identify which of its transcriptional targets contribute to cancer cell proliferation. We first confirmed that ASPSCR1–TFE3 has a predominantly nuclear localization and functions as a stronger transactivator than native TFE3. Genome‐wide location analysis performed on the FU‐UR‐1 cell line, which expresses endogenous ASPSCR1–TFE3, identified 2193 genes bound by ASPSCR1–TFE3. Integration of these data with expression profiles of ASPS tumour samples and inducible cell lines expressing ASPSCR1–TFE3 defined a subset of 332 genes as putative up‐regulated direct targets of ASPSCR1–TFE3, including MET (a previously known target gene) and 64 genes as down‐regulated targets of ASPSCR1–TFE3. As validation of this approach to identify genuine ASPSCR1–TFE3 target genes, two up‐regulated genes bound by ASPSCR1–TFE3, CYP17A1 and UPP1, were shown by multiple lines of evidence to be direct, endogenous targets of transactivation by ASPSCR1–TFE3. As the results indicated that ASPSCR1–TFE3 functions predominantly as a strong transcriptional activator, we hypothesized that a subset of its up‐regulated direct targets mediate its oncogenic properties. We therefore chose 130 of these up‐regulated direct target genes to study in high‐throughput RNAi screens, using FU‐UR‐1 cells. In addition to MET, we provide evidence that 11 other ASPSCR1–TFE3 target genes contribute to the growth of ASPSCR1–TFE3‐positive cells. Our data suggest new therapeutic possibilities for cancers driven by TFE3 fusions. More generally, this work establishes a combined integrated genomics/functional genomics strategy to dissect the biology of oncogenic, chimeric transcription factors. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.